Documentação da arquitetura de sistemas e frameworks para processamento e análise de imagens: uma abordagem baseada em visões da UML e padrões - Estivalete, Patricia Blini (2007)
In the documentation of software architecture, it must be considered two relevant points: i) the architecture is composed by several visions, and ii) each vision identifies a set of components and interactions which allows a better understanding between developers and system programmers. The documentation of the components, when treating reusability, must present a set of information concerning its functionality and applicability in order to adapt them in applications of same domain. When we think of interaction among components, the information concerning the communication messages must be well identified so that the process of working may be clearly understood. This work shows the creation of a catalog of documentation patterns for the architecture of image processing and analysis systems approaching on the concept of design patterns and architecture visions of UML which will be used as the base for designing the Patterns. Through its use, the developers will be more sure of which is necessary to document and safer when reusing components previously tested and documented. It is also shown in this work the development of templates environment of the Patterns in the tool MoinMoinWiki aiming at creating a scenery for collaborative work and also a repository of information on documentation of systems architecture and frameworks within image domain.